2022
DOI: 10.20944/preprints202202.0338.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Artificial Intelligence and Deep Learning in Medical Imaging: A Nationwide Survey of Trainees in Saudi Arabia

Abstract: Artificial intelligence is dramatically transforming medical imaging. We assessed the levels of artificial intelligence use among radiology trainees and explored their perceived impact of artifi-cial intelligence on the radiology workflow and radiology profession, in correlation with the perceived ease of use and behavioral intention to use artificial intelligence. This cross-sectional study enrolled radiology trainees from Saudi Arabia, and an online 5-part-structured question-naire was disseminated via onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…AI is expected to substantially transform radiology in the coming years, with a noticeable impact predicted within 5 years. [29] Respondents saw AI applications as promising for radiology practice but not threatening to the profession. Other studies have also shown AI's potential to transform radiologists' daily work, though whether this will re ne or diminish the radiologist's role remains debated.…”
Section: Discussionmentioning
confidence: 99%
“…AI is expected to substantially transform radiology in the coming years, with a noticeable impact predicted within 5 years. [29] Respondents saw AI applications as promising for radiology practice but not threatening to the profession. Other studies have also shown AI's potential to transform radiologists' daily work, though whether this will re ne or diminish the radiologist's role remains debated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different knowledge levels and attitudes were observed among radiologists in Saudi Arabia. Some studies showed good knowledge of radiologists in AI and ML use in radiography [54,55], while other authors showed low levels of knowledge toward AI [56].…”
Section: Perceptions Towards the Use Of Ai In Radiography In Saudi Ar...mentioning
confidence: 99%
“…Mirza et al [56] that a significant portion of radiology residents felt that AI would lessen the workload in the field of radiology [54], while Qurashi et al [55] stated that over half of radiology staff are worried about the detrimental effects of AI on their field of work.…”
Section: Perceptions Towards the Use Of Ai In Radiography In Saudi Ar...mentioning
confidence: 99%